2021
DOI: 10.1158/0008-5472.can-20-2743
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor β-Mediated Inhibition of Actin-Based Cell Migration Suppresses Metastasis of Inflammatory Breast Cancer

Abstract: Inflammatory breast cancer (IBC) is a highly metastatic breast carcinoma with high frequency of estrogen receptor α (ER)α-negativity. Here we explored the role of the second ER subtype, ERβ, and report expression in IBC tumors and its correlation with reduced metastasis. Ablation

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…3 B). These results are in concordance with another study where higher levels of ERβ were found to be associated with favorable OS in inflammatory breast cancer patients 51 .
Figure 3 ESR2 expression and association to overall survival (OS) and relapse-free interval (RFI) in the full SCAN-B cohort ( A , B ), the endocrine-treated sub-group ( C , D ) and the chemotherapy-treated subgroup ( E , F ).
…”
Section: Resultssupporting
confidence: 93%
“…3 B). These results are in concordance with another study where higher levels of ERβ were found to be associated with favorable OS in inflammatory breast cancer patients 51 .
Figure 3 ESR2 expression and association to overall survival (OS) and relapse-free interval (RFI) in the full SCAN-B cohort ( A , B ), the endocrine-treated sub-group ( C , D ) and the chemotherapy-treated subgroup ( E , F ).
…”
Section: Resultssupporting
confidence: 93%
“…In a recent study, the anti-invasive effect of ERβ agonists was increased by GPER suppression ( Schmitz et al, 2022 ); however, ERβ1 did not directly regulate the expression of GPER mRNA. In ERa-negative inflammatory BC cells, ERβ1 suppresses cell migration via direct suppression of GPR141 expression (another GPCR) ( Thomas et al, 2021 ). Additionally, increased VEGF expression due to increased GPER expression promotes angiogenesis and cancer progression ( De Francesco et al, 2014 ).…”
Section: Mechanism Underlying the Roles Of Erβ Isoforms In Tnbc Progr...mentioning
confidence: 99%
“…ERβ is a ligand activated transcription factor that mediates effects of estrogen, along with ERα in different tissues during growth and development by regulating transcription of target genes. Tumor suppressive effects of ERβ have been documented in diverse cancer types such as thyroid, kidney, prostate, glioblastoma, ovarian and breast cancer [ 5 , 6 ]. A previous scientific report from our group was the first to look at ERβ levels in clinical specimens of IBC patients [ 6 ].…”
mentioning
confidence: 99%
“…Tumor suppressive effects of ERβ have been documented in diverse cancer types such as thyroid, kidney, prostate, glioblastoma, ovarian and breast cancer [ 5 , 6 ]. A previous scientific report from our group was the first to look at ERβ levels in clinical specimens of IBC patients [ 6 ]. Immunohistochemical analysis of IBC tumors revealed the association of higher expression of ERβ with significant improvement in metastasis free survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation